Chapter 18: Salmon farming firms moving towards resource circularity: a typology of resource loop innovations - Wigger, Karin (Edward Elgar Publishing, 2021)
The transition towards resource circularity requires firms to use resources that circulate in sustainable resource loops instead of adapting the 'take-make-use-dispose' approach. Resource circularity asks for innovative resource loop solutions within and between firms. Through an abductive study of innovation projects developed by Norwegian salmon farming firms, this chapter offers a typology matrix consisting of seven types of resource loop innovations. We propose that firms develop resource loop innovations to reconfigure resource services of inbound, inhouse, and outbound resources, minimize the use of unproductive resources of inbound and outbound resources, and expand the range of resource services of inhouse resources. Through these resource loop innovations, negative externalities are minimized and underutilized resources re-used, which leads to increased resource circularity and more sustainable industries.